2019
DOI: 10.5114/pedm.2019.85814
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of vitamin D concentrations and the incidence of vitamin D deficiency in children and adolescents from central Poland

Abstract: Introduction: Vitamin D 3 [25(OH)D] deficiency is a significant problem in Polish children. In many regions of the world, 25(OH)D concentrations show seasonal variation and differences between boys and girls, due to seasonal differences in insolation, as well as different sociological and cultural factors. The aim of the study was to assess the seasonal variations of 25(OH)D concentrations and the incidence of vitamin D deficiency in children from central Poland. Material and methods: The analysis comprised 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…As for seasons the highest values were in summer-July, August, September, and lowest in winter-January, February, March, with no difference between autumn and spring [19]. The level of insolation in previous months remained in close relationship with 25(OH)D levels and in Polish children a two-month shift was observed between the highest insolation and maximal 25(OH)D level [19]. This is due to long half-life of serum 25(OH)D. Indeed, the highest insolation in Poland is observed in May (4.97 kWh/m 2 /day) and the lowest in December (0.67 kWh/m 2 /day), which confirms the two-month shift.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As for seasons the highest values were in summer-July, August, September, and lowest in winter-January, February, March, with no difference between autumn and spring [19]. The level of insolation in previous months remained in close relationship with 25(OH)D levels and in Polish children a two-month shift was observed between the highest insolation and maximal 25(OH)D level [19]. This is due to long half-life of serum 25(OH)D. Indeed, the highest insolation in Poland is observed in May (4.97 kWh/m 2 /day) and the lowest in December (0.67 kWh/m 2 /day), which confirms the two-month shift.…”
Section: Discussionmentioning
confidence: 87%
“…In the study of Smyczyńska el al. (n = 1275) the highest concentrations of 25(OH)D were observed in August (incidence of deficiency was 10.7%) and minimal in January (incidence of deficiency was 80.4%) [19]. As for seasons the highest values were in summer-July, August, September, and lowest in winter-January, February, March, with no difference between autumn and spring [19].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…From other studies, it is known that in countries such as Poland, skin synthesis of vitamin D is observed only from April to October (if the sunshine exposure is adequate) [20]. According to a recent Polish study [43], the highest levels of 25(OH)D in Poland are observed in August and the lowest in January, which could be explained by insolation and 25(OH)D synthesis during summer and the mobilization of vitamin D stored in the body (during the summer months) in the winter.…”
Section: Discussionmentioning
confidence: 99%